Empirical determinants of employee resistance against innovations - Zwick, Thomas (ZEW, 2000)
Employee resistance against innovations is a virulent phenomenon and there is a broad theoretical literature on its determinants. The empirical evidence is scarce, however, and mainly provides descriptive evidence on the incidence of the phenomenon and concentrates on the effectiveness of change management as a measure against it. A second branch of the empirical literature investigates the impact of unions on adoption costs and the successful implementation of innovations. There is no representative evidence on the impact of the economic environment on employee opposition against the implementation of an innovation in the firm independent of managerial activities, however. This paper uses a unique firm-level data set of a representative sample of German service firms which includes detailed information on the economic environment of the firm. It shows that employee opposition against innovations can be predicted by very basic information on the firm that is relevant for the economic situation of the employees. Employee opposition is smaller in firms whose generic business strategy is differentiation, while it is larger in firms aiming at gaining competitive advantage by low costs and prices. If the goals of the innovation is an increase in employee performance, the firm experiences higher resistance, while resistance is lower in firms aiming at increasing the product range by the innovation. Profit and turn over expectations of the firm and the outside option of the employees are negatively correlated with employee resistance. Finally, smaller firms and firms operating in the computer and software or the technical consulting sector experience lower employee resistance. Therefore, the focus on change management measures or union activities in order to predict employee resistance against innovations seems too narrow.
Literaturverz. S. 14 - 16
Keywords: Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Innovation; Arbeitsbeziehungen; Betriebswirtschaftliches Ziel; Betrieblicher Konflikt; Schätzung; Dienstleistungssektor; Deutschland; Innovationswiderstände